The Patriotic war of 1812 in the book collection of N. K. Shilder: books with autographs - О. В. Полевщикова (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Bìblìotekoznavstvo, Bìblìografoznavstvo, Knigoznavstvo, 2014)
Memorials of 1812 conserved in the stocks of the Scientific Library of the Odesa I. I. Mechnikov National University are considered in the framework of the Jubilee events devoted to the 200th anniversary of the victory of Russian arms in the Patriotic War of 1812. The purpose of the article is to examine the copies of books on the Patriotic War of 1812 bearing autographs. More than 150 publications on Napoleonic wars (official documents, memories, pamphlets, verse, speeches etc.) coming from the book collection of a famous Russian historian N. K. Shilder (1842-1902) have been revealed and examined de visu. Some facts on the biography and activities of N. K. Shilder as well as his library and the history of its delivery to Novorossiiskiy University are given. The finding of the article is represented by the information on the copies of books printed in the first third of the 19th century bearing autographs – both dedicatory inscriptions and owners’ recordings – which enables to enlarge the database of provenance making the practical value and results of the research.